AVALIAÇÃO DA APLICAÇÃO DE CINZAS PESADAS DE TERMELÉTRICA EM BLOCOS INTERTRAVADOS DE CONCRETO PARA PAVIMENTOS - Silva, Webert; Barroso, Suelly; Cabral, Antônio (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
In order to study the behavior of concrete in interlocking blocks for paving, it was decided to incorporate bottom ashes, which are residues generated significantly by means of a thermoelectric plant, in the composition of the same concrete. After the collection of conventional and alternative materials, physical characterization tests were performed. By means of the granulometric stabilization, an alternative ash and a conventional aggregate reference traces were used. After the production of the concrete, this, in the hardened state, was subjected to the compressive strength and water absorption tests. It is concluded that the results obtained, from the experimental program, encourage the use of bottom ashes on interlocked concrete pavements.